Experimental and numerical analysis of RC two-span slabs strengthened with NSM CFRP laminates - Dalfré, Gláucia (2011)
This work reports the results of an ongoing research program on the use of the near surface mounted (NSM) CFRP laminates for the flexural strengthening of continuous reinforced concrete (RC) slabs. The experimental program is formed by two slab strips of two equal span lengths, and has the main purpose of verifying the possibility of increasing the negative resisting bending moment in 25%, maintaining a relatively high level of moment redistribution. To assess the predictive performance of a FEM-base computer program, the experimental results are compared with the values estimated by the numerical analysis carried out using a FEM-based computer program. The results show that the proposed strengthening technique is able to increase significantly the load carrying capacity of RC slabs. However, the load carrying capacity of the strengthened slabs was limited by the detachment of the strengthened concrete cover layer at the intermediate support. The numerical model predicts with high accuracy the behavior of this type of structures.